Le discours antinobiliaire en Espagne à la fin du XVIIIe et dans la première moitié du XIXe siècle - Arnaud Pierre (Cahiers de Civilisation Espagnole Contemporaine)
Since the end of the 18th-century at least, there were many in Spain who strongly criticized some hidalgos, although they did not question the existence of gentry. These hidalgos were seen as idle, poor and useless to society. In the first half of the 19th-century, this critical discourse broadened and became an attack on the “aristocracy”, which can be considered to be holders of a title (título de Castilla). If this criticism is not surprising coming from progresistas liberals, it is more so coming from moderados or even more conservative opinions. This article aims at being a contribution to the History of early-19th-century Spanish political cultures, and analyses the hostile discourse towards nobility during this period. It will study how this dominant discourse shaped the society which came from the Spanish revolution.